Bronchiectasis in Children: Current Concepts in Immunology and Microbiology - Pizzutto, Susan J.; Hare, Kim M.; Upham, John W. (Frontiers in Pediatrics, 2017)
Bronchiectasis is a complex chronic respiratory condition traditionally characterized by chronic infection, airway inflammation, and progressive decline in lung function. Early diagnosis and intensive treatment protocols can stabilize or even improve the clinical prognosis of children with bronchiectasis. However, understanding the host immunologic mechanisms that contribute to recurrent infection and prolonged inflammation has been identified as an important area of research that would contribute substantially to effective prevention strategies for children at risk of bronchiectasis. This review will focus on the current understanding of the role of the host immune response and important pathogens in the pathogenesis of bronchiectasis (not associated with cystic fibrosis) in children.